Impact of Docosahexaenoic Acid Therapy on Subgingival Plaque Microbiota. Issue 9 (1st September 2017) - Naqvi, Asghar Z.; Mu, Lin; Hasturk, Hatice; Van Dyke, Thomas E.; Mukamal, Kenneth J.; Goodson, J. Max
Abstract : Background: Oral docosahexaenoic acid (DHA) + aspirin therapy has been shown to reduce periodontal probing depth (PD) and local inflammatory mediators in gingival crevicular fluid (GCF) among patients with untreated chronic periodontal disease. Whether DHA + aspirin therapy influences specific bacterial burden in this setting is unknown. Thus, the aim of this study is to evaluate the impact of DHA with low‐dose aspirin therapy on periodontal bacterial profile in patients with periodontitis. Methods: Fifty‐five adults with moderate‐to‐severe periodontitis were enrolled in a randomized, 3‐month double‐masked, placebo‐controlled trial of daily 2 g DHA or placebo capsules enriched with 81 mg aspirin; 46 enrollees completed the trial. In addition to clinical measurements and GCF sampling, subgingival plaque samples were collected from four posterior sites in all participants and analyzed by the checkerboard DNA–DNA hybridization technique. Presence of 40 periodontal bacterial species at baseline and 3 months was semiquantitatively estimated. Results: Despite broad improvements in clinical parameters, total bacteria and individual species counts in dental plaque did not differ significantly between baseline and 3 months in either group ( P >0.1 for all). A modest effect of DHA + aspirin on Porphyromonas gingivalis counts was associated with 14% (95% confidence interval: 3% to 35%) of the observed benefit of DHA on PD. DHA + aspirin had no significant effect on individual plaque bacterial counts in unadjusted models or those adjusted for age, sex, and race ( P >0.1 for all). Conclusions: This pilot randomized, controlled trial suggests that DHA + aspirin therapy improves periodontitis largely by modulating host inflammatory response. Changes in individual species levels in subgingival plaque microbiota were not detectable; however, a small portion of the benefit appears to stem from changes in P. gingivalis levels in the DHA + aspirin treatment group. Whether this change in P. gingivalis levels leads to biofilm alteration with reversal of dysbiosis requires further longitudinal and more specific investigations.